Analisis Yuridis Perjanjian Jual Beli Tanah Dan Bangunan Dengan Hak Membeli Kembali (Studi Putusan Mahkamah Agung NO. 925 PK/PDT/2019) - Pasaribu, Efrilla Azizah (Universitas Islam Sumatera Utara, 2023)
An authentic deed has complete evidentiary power which contains the legal actions of the parties as the embodiment of the will of the parties. The existence of a discrepancy between the will and the statement can cause legal uncertainty for the parties, especially in sale and purchase where the will of debt and receivables is converted into a sale and purchase. In this case, the sale and purchase agreement with the right to repurchase is commonly used in the community to cover a debt and often causes problems. Based on this, the problems raised in this thesis research are how the legal position of the Sale and Purchase Binding Deed with the right to repurchase which is covered by a account receivables correlation, how is the legal analysis of the judges’ considerations in this decisions at each level of justice and what are the legal consequences and liability of the notary to the Sale an Purchase Binding Deed with the right to repurchase which he made is canceled by the court because it contained elements of an unlawful act. This research employs normative juridical research method using a qualitative approach and descriptive analysis. The data used to answer the problems in this research are primary data and secondary data derived from document studies and interview guidelines. The research results show that legal position of the Sale and Purchase Binding Deed accompanied by an agreement with the right to repurchase which is shrouded in a account payable correlation is invalid and has no binding legal force so that is null and void because it is considered a quast/simulation agreement where there is a conflict between the will and the parties agreement. The legal consequence of a deed that has been canceled by the court because it contains elements of an unlawful act is that the deed has no binding legal force and is degraded into an underhand deed so that the notary must be responsible for the mistake. Notaries should apply the precoutionary principle to minimize mistakes in making the Deed, especially regarding sale and purchase agreements with the right to repurchase which have a high risk of legal smuggling. Notaries must have honesty, act carefully, ptotect the interests of the parties and provide legal counseling for those who come to them as mandated in the Law of Notary Positions. Keyword : agreements, sale and purchase of land, the rights to repurchase